2014
DOI: 10.1016/j.pain.2014.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of pain-related self-management for cancer patients through a modular transitional nursing intervention: A cluster-randomized multicenter trial

Abstract: Patients' self-management skills are affected by their knowledge, activities, and attitudes toward pain management. This trial aimed to test the Self Care Improvement through Oncology Nursing (SCION)-PAIN program, a multimodular structured intervention to reduce patients' barriers to self-management of cancer pain. Two hundred sixty-three patients with diagnosed malignancy, pain>3 days, and average pain > or = 3/10 participated in a cluster-randomized trial on 18 wards in 2 German university hospitals. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(95 citation statements)
references
References 44 publications
1
89
1
4
Order By: Relevance
“…The study population varied from 30 to 1256 patients at baseline. Twelve studies were conducted in the USA [18,[23][24][25][26][27][28][29][30][31][32][33], eight in Europe [20,21,[34][35][36][37][38][39], three in Asia [40][41][42], two in Australia [43,44] and one in Canada [45].…”
Section: Resultsmentioning
confidence: 99%
“…The study population varied from 30 to 1256 patients at baseline. Twelve studies were conducted in the USA [18,[23][24][25][26][27][28][29][30][31][32][33], eight in Europe [20,21,[34][35][36][37][38][39], three in Asia [40][41][42], two in Australia [43,44] and one in Canada [45].…”
Section: Resultsmentioning
confidence: 99%
“…Earlier intervention studies on patients with cancer support our findings that SC had no significant impact on cancer pain [104,105,211] while other studies have shown that SC does reduce pain [212,213]. It is possible that hetero/homogeneity (participants and interventions) in the studies referred to above may have contributed to the different conclusions.…”
Section: Self-caresupporting
confidence: 69%
“…The previously developed S elf C are I ntervention in O ncology N ursing (Jahn et al . , , ) was adapted for patients undergoing H ematopoietic S tem C ell T ransplantation, (SCION‐HSCT) by the authors in cooperation with nurses of the University Hospital Halle Saale as conceptual framework for this study.…”
Section: Methodsmentioning
confidence: 99%